2023
DOI: 10.1007/s13346-023-01379-8
|View full text |Cite
|
Sign up to set email alerts
|

A two-pronged approach against glioblastoma: drug repurposing and nanoformulation design for in situ-controlled release

Maria Mendes,
Francisco Branco,
Rui Vitorino
et al.

Abstract: Glioblastoma (GB) is one of the most lethal types of neoplasms. Its biologically aggressive nature and the presence of the blood–brain barrier (BBB) limit the efficacy of standard therapies. Several strategies are currently being developed to both overcome the BBB and deliver drugs site specifically to tumor cells. This work hypothesizes a two-pronged approach to tackle GB: drug repurposing with celecoxib (CXB) and a nanoformulation using ultra-small nanostructured lipid carriers (usNLCs). CXB antitumor drugga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…The observed profile of toxicity, proliferation, apoptosis, and migration are consistent with those obtained by others. Celecoxib significantly destroyed A172 glioma cells via the apoptosis pathway after 24 h incubation from 25 µM concentration upward [ 46 ]. In a mouse model of malignant glioma (glioma stem cells GSC), celecoxib was toxic (IC 50 = 60 µM), with overexpression of apoptosis marker (cleaved PARP and caspases) [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed profile of toxicity, proliferation, apoptosis, and migration are consistent with those obtained by others. Celecoxib significantly destroyed A172 glioma cells via the apoptosis pathway after 24 h incubation from 25 µM concentration upward [ 46 ]. In a mouse model of malignant glioma (glioma stem cells GSC), celecoxib was toxic (IC 50 = 60 µM), with overexpression of apoptosis marker (cleaved PARP and caspases) [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…The latest studies on the effect of celecoxib on four glioma cell lines (U87, U-118 MG, H4, and A172) after 24 h of incubation showed that the IC 50 values for celecoxib ranged from 100 to 400 µM; U-118 MG cells turned out to be the most resistant (IC 50 around 400 µM). Cell death occurred by apoptosis [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…The Quality Target Product Profile (QTPP) is a fundamental element of the QbD approach, wherein the essential attributes a drug product should attain are prospectively summarized envisioning the quality features intended to be reached, with a focus on ensuring the safety and efficacy of the drug product (Mendes et al, 2023;Step, 2017). A risk estimation matrix (REM) was constructed to identify and prioritize potential high-risk process parameters that could influence the critical quality attributes.…”
Section: Quality Target Product Profile and Initial Risk Assessmentmentioning
confidence: 99%